Male Genitalia of some Nepalese Species Onthophagus Latreille (Coleoptera: Scarabaeidae) - Mahato, Shyam Prasad (Journal of Natural History Museum, 2015)
The present paper deals with the studies of male genitalia of Onthophagus Latreille, the common dung beetle of Nepal. The male genitalia are described and illustrated for 9 species of Onthophagus Latreille –O. pactolus (F.), O. aenescens (Wied.), O. ramosellus Bates, O. sternalis Arrow, O. catta (F.), O. bonasus (F.), O. rectecornutus Lansb., O. atropolitus d'Orb., O. sagittarius F. of Nepal. The male genitalia of these species were found to be consisting of phallobase, parameres, aedeagus and endophallus similar to those of the other genera of Coprinae and primitive in their main features. J. Nat. Hist. Mus. Vol. 26, 2012: 88-92